“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Explaining Machines: Social Management of Incomprehensible Algorithms. Introduction - Esposito, Elena (Sociologica)
This short introduction presents the symposium ‘Explaining Machines’. It locates the debate about Explainable AI in the history of the reflection about AI and outlines the issues discussed in the contributions.
Keywords: Explainable AI; Inexplicability; Transparency; Explanation; Opacity; Contestability

End-to-End Dereverberation, Beamforming, and Speech Recognition in A Cocktail Party - Zhang, Wangyou; Chang, Xuankai; Boeddeker, Christoph; Nakatani, Tomohiro; Watanabe, Shinji; Qian, Yanmin (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Far-field multi-speaker automatic speech recognition (ASR) has drawn increasing attention in recent years. Most existing methods feature a signal processing frontend and an ASR backend. In realistic scenarios, these modules are usually trained separately or progressively, which suffers from either inter-module mismatch or a complicated training process. In this paper, we propose an end-to-end multi-channel model that jointly optimizes the speech enhancement (including speech dereverberation, denoising, and separation) frontend and the ASR backend as a single system. To the best of our knowledge, this is the first work that proposes to optimize dereverberation, beamforming, and multi-speaker ASR in a fully end-to-end manner. The frontend module consists of a weighted prediction error (WPE) based submodule for dereverberation and a neural beamformer for denoising and speech separation. For the backend, we adopt a widely used end-to-end (E2E) ASR architecture. It is worth noting that the entire model is differentiable and can be optimized in a fully end-to-end manner using only the ASR criterion, without the need of parallel signal-level labels. We evaluate the proposed model on several multi-speaker benchmark datasets, and experimental results show that the fully E2E ASR model can achieve competitive performance on both noisy and reverberant conditions, with over 30% relative word error rate (WER) reduction over the single-channel baseline systems.

Group work and student procrastination - Koppenborg, Markus; Klingsieck, Katrin B. (Learning and Individual Differences)
Keywords: Developmental and Educational Psychology; Education; Social Psychology

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

Classification of visuomotor tasks based on electroencephalographic data depends on age-related differences in brain activity patterns - Gölz, Christian Johannes; Mora, K.; Rudisch, J.; Gaidai, Roman; Reuter, E.; Godde, B.; Reinsberger, Claus; Voelcker-Rehage, C.; Vieluf, S. (Neural Networks)
Keywords: Artificial Intelligence; Cognitive Neuroscience

Classification of visuomotor tasks based on electroencephalographic data depends on age-related differences in brain activity patterns - Goelz, C.; Mora, K.; Rudisch, J.; Gaidai, R.; Reuter, E.; Godde, B.; Reinsberger, Claus; Voelcker-Rehage, C.; Vieluf, S. (Neural Networks)
Keywords: Artificial Intelligence; Cognitive Neuroscience

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Reciprocal effects between self-concept of ability and performance: A longitudinal study of children with learning disabilities in inclusive versus exclusive elementary education - Gorges, Julia; Neumann, Phillip; Wild, Elke; Stranghöner, Daniela; Lütje-Klose, Birgit (Learning and Individual Differences)
Ample empirical research from regular school settings documents reciprocal effects between academic performance and academic self-concept of ability (ASC), supporting what is known as a reciprocal effects model (REM). The present article investigates a REM in the domain of reading performance in a sample of elementary students with special educational needs in learning (SEN-L) who received special educational support in exclusive versus inclusive settings (N = 446). In exclusive settings, SEN-L students attend special schools and are completely separated from regular students. By contrast, SEN-L students in inclusive settings attend regular schools and are educated in classes with regular students. In both settings, SEN-L students are not graded and taught based on individual learning goals, which may affect reciprocal effects between ASC and reading performance. In addition, given that special education for SEN-L students relies heavily on individual reference standards to evaluate performance, we tested individual performance growth of SEN-L students as a predictor of ASC. Analyses of a longitudinal dataset across 3rd and 4th grade revealed some cross-lagged effects and an effect of performance growth on ASC in exclusive settings in particular. The discussion focuses on the role of individualized instruction, grades, peer groups, and individual versus social reference standards for reciprocal effects between ASC and performance as well as practical implications.
Keywords: BiLieF; Special educational needs; Learning disability; Academic selfconcept of ability; Reciprocal effects model; Inclusive education

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

On the assessment of attitudes towards studying—development and validation of a questionnaire - Brahm, Taiga; Jenert, Tobias (Learning and individual differences : journal of psychology and education)
This research aims to develop and validate an instrument for the assessment of attitudes towards two particular objects: the Higher Education Institution (HEI) and the process of studying. Investigating attitudes towards studying at a HEI in a comprehensive way addresses an important research gap. It connects students' perception of the institution with teaching and learning. To validate the Assessment of Students' Attitudes towards Studying (ASAtS) Questionnaire, data was gathered at three different universities in Switzerland (820 students), Sweden (167) and Germany (133). Overall, the results show the internal consistency of the ASAtS. Its nomological validity is also supported by correlations with other constructs, such as intrinsic motivation and study performance. The ASAtS contributes to the theory on students learning by broadening the scope of research beyond learning in a narrow sense. From a practical point of view, it provides a tool for HE management to monitor students' perception of their HEI.
Keywords: Attitude; Student learning; Higher Education Institution; university; student experience

Assessing cognitive alignment in different types of dialog by means of a network model - Mehler, Alexander; Lücking, Andy; Menke, Peter (Neural Networks)

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)